MOTIVATION OF ACCEPTORS KB IN ELECTION IUD CONTRACEPTION - nurhayati, enur (STIKES dan AKZI Karya Husada Kediri, 2023)
The IUD is one of the most effective and safe long-term contraceptives compared to other contraceptives. Until now, the use of IUDs is still very low among women of childbearing age (WUS). The use of IUD KB is an alternative choice as a tool for family planning, however this is often avoided and becomes a compulsion because of the side effects experienced by KB acceptors. However, this contraception can be an alternative last resort for (WUS) who have limitations due to health, even though there are many side effects that (WUS) will experience. The purpose of community service is to provide knowledge and motivation for IUD family planning acceptors in choosing IUD contraception. Education or counseling will be held from 27 March to 2 April 2023. At RT 02 RW 02 Sumur Cinde Village, Soko District, Tuban Regency, East Java. This activity was attended by 26 participants of reproductive age women. the implementation of the activity was assisted by 2 students. The method used is lecture, discussion/question and answer. Implementation of activities using leaflet media, providing material using LCD media and laptops. The results of interviews and filling out questionnaires by activity participants regarding the motivation of family planning acceptors in choosing IUD contraception. Obtained Almost all respondents as much as 77% have high motivation, a small proportion of respondents as much as 23% have moderate motivation. The motivation for women of childbearing age in choosing contraception must be seen for themselves whether the contraception chosen has provided a sense of security, comfort, according to their needs and in accordance with their health.